The relationship between unemployment and alcoholism (Research, Society and Development, 2022)
To understand the relationship between unemployment and the substantial increase in the number of cases of alcoholism, in order to help create intervention measures concerning this problem. Medicine usually deals with disease patterns that are closely linked to the existing social environment, and may vary according to cultural and religious aspects of certain ethnic groups and regions of the earth. Thus, it is urgent to think about the relationship between unemployment and the substantial increase in the number of cases of alcoholism, since alcohol abuse is increasingly common among people included in the productive life and causes not only personal and family losses, but also damages in the professional environment, such as increased absenteeism and greater likelihood of accidents at work, bringing deleterious effects on the individual's health. Given the cultural importance historically established to work, unemployment can generate a life without meaning and a situation of social vulnerability, which can cause a symbolic and psychic disorder, leading to the development of alcoholism.